MODELING OF PROCESS OF THE WIRE SLUGS CONTINUOUS VERTICAL CASTING - E. I. Marukovich; V. A. Pumpur; V. A. Harkov (Литьë и металлургия)
The mathematical model of heat-exchange and program complex for modeling o f the process o f the wired slug forming at continuous vertical casting are presented. The possibilities of software support and form of presentation of the calculation results are described.